Pontoppidans Lykke-Per: – og den stendhalske impuls - Vangshardt, Mie (Pontoppidaniana, 2025)
Abstract The present article examines the literary kinship between Henrik Pontoppidan and Stendhal through a study of the concept of happiness in the novels Lykke-Per (1905) and Le Rouge et le Noir (1830). Both considered realistic-naturalistic masterpieces, the article reveals an undercurrent of longing, withdrawal, irony and metaphysical interpretation of fate in the concept of happiness, which leads to a reconsideration of the novels’ embeddedness in the literary tradition of Romanticism.